AGENTES INTELIGENTES PARA DETECÇÃO DE INTRUSOS EM REDES DE COMPUTADORES - Lima, Christiane Ferreira Lemos (2002)
Recently, the interest for advanced techniques for network intrusion detection have been increased for protecting important information in computational environment. This research work presents a proposal of a new network intrusion detection system based on a society of intelligent agents whose reasoning are aupported by neural network paradigms, named NIDIA (Network Intrusion Detection System based on Intelligent Agents). A computational implementation has been carried out for the network and host sensors for dealing with task of capturing packets related to suspicious connections or abnormal behaviors within critical hosts.